DESIGN OF FABRIC WASTE MANAGEMENT INFORMATION SYSTEM FOR CIRCULAR ECONOMY NONPROFITS - Kiki Puspo Arianty; Mila Anjani (Journal of Economic, Bussines and Accounting (COSTING), 2026)
Textile waste management based on the circular economy still faces challenges related to material flow documentation, distribution accountability, and stakeholder coordination, particularly within nonprofit organizations. This study aims to design and develop the SILAHKAN information system as a solution to support structured, transparent, and sustainable textile waste management. The research adopts applied research with a qualitative descriptive approach combined with system development research. Data were collected through interviews, observations, documentation, and literature review. System development was conducted using the Agile Software Development method, encompassing problem identification, requirements analysis, system design, iterative development, testing, and user based evaluation. The results indicate that the SILAHKAN system supports textile waste flow recording, improves distribution traceability, and strengthens the role of nonprofit organizations as key actors in circular economy implementation. The system is expected to serve as an adaptive and practical information technology based model for textile waste management in nonprofit organizations.